Elimination of staphylococcus aureus in hemodialysis patients - Bommer, Jürgen; Vergetis, Wassilios; Andrassy, Konrad; Hingst, V.; Borneff-Lipp, Marianne; Huber, W. (ASAIO journal, 1995)
Staphylococcus aureus infection and its complications are of great concern in the care of hemodialysis patients. Nasal contamination with S. aureus seems to be the main source of cutaneous contamination. The decontamination and recontamination of the skin of hemodialysis patients after using mupirocin nasal ointment was followed in a placebo control study. After 10 days of therapy with mupirocin nasal ointment, 25 of 33 (73%) patients were free of nasal S. aureus contamination in the nares (control subjects 2 of 21, 10%). At the same time, the prevalence of positive skin cultures for S. aureus decreased from 30 of 33 (90%) to 11 of 33 (33%) patients. However, during the ensuing 130 days, 14 of 25 (58%) patients with negative nasal cultures became recontaminated, while the skin became recontaminated in 11 of 22 (50%) patients. - In 10 of 14 S. aureus recontaminated patients the original S. aureus lysotype was documented by specific phage reaction. Four of fourteen patients had a new S. aureus lysotype. Mupirocin nasal ointment eradicated S. aureus transiently in 75% of the patients but continuously in only 11 of 33 (30%) patients.
Gesehen am 25.10.2023